EDUCATIONAL PERCEPTIONS IN THE USE OF “STORYTELLING” - Holtz, Marcelo Martins (Seven Editora, 2026)
This work aims to understand the use of storytelling and its contributions to the teaching and learning process, considering the benefits and applicability. To this end, initially the definition of the term was reflected upon, as well as the concept of strategy, and only then could the possible benefits that can be extracted from this educational cycle be mentioned. In short, with this tool, the educator adopts a certain strategy to tell a story to students, with the intention of transmitting the intended information by creating an emotional connection. To this end, bibliographical research was carried out using experts on the subject, and in this way, three possible benefits of using the storytelling resource were found, consisting of retaining the student's attention; the creation of a social and empathetic environment; and the possibility of the content becoming more accessible, meaningful and memorable, which can awaken the student's attention, empathy and meaning, important concepts that can contribute to the assimilation of what is being taught.DOI: https://doi.org/10.56238/sevened2026.001-009